Gastroesophageal Reflux Disease Outcomes After Vertical Sleeve Gastrectomy and Gastric Bypass. Issue 4 (October 2021) - Leslie, Daniel; Wise, Eric; Sheka, Adam; Abdelwahab, Hisham; Irey, Ryan; Benner, Ashley; Ikramuddin, Sayeed
Abstract : Objective: The objective of this study is to assess whether vertical sleeve gastrectomy (VSG) increases the incidence of gastroesophageal reflux disease (GERD), esophagitis and Barrett esophagus (BE) relative to patients undergoing Roux-en-Y gastric bypass (RYGB) in patients with and without preoperative GERD. Summary of Background Data: Concerns for potentiation of GERD, supported by multiple high-quality retrospective studies, have hindered greater adoption of the VSG. Methods: From the OptumLabs Data Warehouse, VSG and RYGB patients with ≥2 years enrollment were identified and matched by follow-up time. GERD [reflux esophagitis, prescription for acid reducing medication (Rx) and/or diagnosis of BE], upper endoscopy (UE), and re-admissions were evaluated beyond 90 days. Results: A total of 8362 patients undergoing VSG were matched 1:1 to patients undergoing RYGB, on the basis of post-operative follow-up interval. Age, sex, and follow-up time were similar between the 2 groups ( P > 0.05). Among all patients, postoperative GERD was more frequently observed in VSG patients relative to RYGB patients (60.2% vs 55.6%, respectively; P < 0.001), whereas BE was more prevalent in RYGB patients (0.7% vs 1.1%; P = 0.007). Postoperatively, de novo esophageal reflux symptomatology was more common in VSG patients (39.3% vs 35.3%; P < 0.001), although there was no difference in development of the histologic diagnoses reflux esophagitis and BE. Furthermore, postoperative re-admission was higher in the RYGB cohort (38.9% vs 28.9%; P < 0.001). Conclusions: Compared to RYGB, VSG may not have inferior long-term GERD outcomes, while also leading to fewer re-hospitalizations. These data challenge the prevailing opinion that patients with GERD should undergo RYGB instead of VSG. Abstract : Supplemental Digital Content is available in the text